ONLINE THESIS GUIDANCE INFORMATION SYSTEM (SI-BISA) TO IMPROVE THE EFFECTIVENESS OF THESIS GUIDANCE ACTIVITIES AT THE UNIVERSITY OF TECHNOLOGY MATARAM - Juhartini, Juhartini; Arwidiyarti, Dwinita; Hambali, Hambali (Jurnal Pilar Nusa Mandiri, 2021)
The Covid-19 pandemic has hit the whole world since the beginning of 2020, making many activities unable to run as usual. Likewise, the thesis mentoring process, which is usually carried out face-to-face with the supervisor by the agreed schedule, is no longer possible due to an appeal from the government to work and study from home so that the mentoring process becomes constrained. Instead, the mentoring process through e-mail or WhatsApp application, where the supervisor will correct the thesis, provide notes for improvement, and send it back to students. E-mail and WhatsApp as media in the mentoring process is used. However, it will make it difficult for lecturers to find out recordings of the student. Besides, it is still possible for thesis files to be scattered or lost because there is only one student. The research aims to produce an online thesis guidance application called SI-BISA. The research was conducted using the Waterfall Model, resulting in the SI-BISA application in the PHP Programming Language with the CodeIgniter 4 Framework. The system design used the Unified Modeling Language and system testing using the Black Box Method. Given the long-lasting Covid-19 pandemic, an online thesis guidance application is very urgent. So that the thesis mentoring process can continue to run effectively even without face-to-face and the need to build an integrated information system to make it easier for supervisors to monitor the progress of their guidance students and improve the effectiveness and service of thesis guidance provided to students.